2014
DOI: 10.2147/amep.s66264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of computer-based treatment planning software on clinical judgment of dental students for planning prosthodontic rehabilitation

Abstract: PurposeSuccessful prosthodontic rehabilitation involves making many interrelated clinical decisions which have an impact on each other. Self-directed computer-based training has been shown to be a very useful tool to develop synthetic and analytical problem-solving skills among students. Thus, a computer-based case study and treatment planning (CSTP) software program was developed which would allow students to work through the process of comprehensive, multidisciplinary treatment planning for patients in a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…A similar clinical study reported that the use of computer-based treatment planning software resulted in improved clinical decision-making skills among dental students. 9 The results of our study were in agreement with those results: a positive association between the use of the software program and improved students’ performance was established from our study.…”
Section: Discussionsupporting
confidence: 92%
“…A similar clinical study reported that the use of computer-based treatment planning software resulted in improved clinical decision-making skills among dental students. 9 The results of our study were in agreement with those results: a positive association between the use of the software program and improved students’ performance was established from our study.…”
Section: Discussionsupporting
confidence: 92%
“… Observations of authentic doctor-patient interactions by different educators in different situations; feedback on different clinical pictures at different locations each with a different focus [ 155 ] Thorough planning is necessary because giving feedback takes 8-17 minutes [ 155 ], [ 160 ]. Relatively simple to implement with enough flexibility in the dental setting [ 161 ] Practical examples exist [ 162 ]. …”
Section: Discussionmentioning
confidence: 99%
“… Reliability depends heavily on the number of assessors and cases [ 151 ], [ 153 ]. Several documented instances in the literature of use in dental medicine (Dental Foundation Training in Great Britain), however, often without any precise information on the evaluation instruments [ 161 ], [ 162 ]. …”
Section: Discussionmentioning
confidence: 99%
“…Level 2 involves modification of attitude and behaviors of learners which was also found to be significantly improved after use of this software. [ 14 ] The present investigation dealt with level 3 that is, investigating whether learning has occurred by the acquisition of knowledge per se . This blended approach should, therefore, be implemented in undergraduate training to improve clinical decision-making while planning prosthodontic rehabilitation.…”
Section: Discussionmentioning
confidence: 99%